An Analytical Study of Qualities of Sufism; In Light of Si Harfi of Peer Naik Alam Shah: کیفیات تصوف کا جائزہ: پیر نیک عالم شاہ کی سی حرفی کی روشنی میں - Hafiz, Muhammad; Rizwan Younas, Dr. Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Sufism has put great impact on human nature. By educating the masses and deepening the spiritual concerns of the Muslims, Sufism has played an important role in the formation of Muslim society. Sufism shares some important spirit and has a great impact of its internal spirit on human. Peer Naik Alam Shah is one of the greatest Sufi poets of Azad Jammu and Kashmir. He lived a life of saint and served humanity through his teachings and poetry. In his poetry, Peer Naik Alam Shah discussed different qualities of Sufism. He discussed different terms related to love of Allah, love of Holy Prophet, Devotion, Respect and other similar terms. He discussed all these in light of Sharia. His book “Si Harfi” ( in light of 30 letters of alphabets of Arabic Language) is replete with sufi related terms.